Comparative analysis between Chinese male and female judo athletes from amateur and professional level through various motor tests - Pecev, S.; Georgiev, G.; Yin, X.; Hristovski, R. (Journal Pedagogical Almanac, 2020)
The aim of this study was to examine the differences in anthropometrics and various motor skills in Chinese amateur and professional level judokas from different genders. For the investigation total of 37 athletes, amateur (male (n=10), aged 15.26±1.6), female (n=3), aged 16.27±0.7) and professional (male (n=17), female (n=7), aged 18+) Participating athletes underwent a comprehensive testing procedure, encompassing assessments for height, weight, a 30-meter sprint, 1RM Bench Press, 1RM Squat, Isometric Hold using Judogi, Ab Hold, and Biering-Sorenson Hold. The results showed that professional judokas were heavier than their amateur counterparts, and performed better in the 1RM bench press, 30-meter sprint as well as in the Ab Hold test. Overall, this study provides insight into the understanding of physical differences between amateur and professional level judokas, offering information that may have implications for further training and development of upcoming athletes in this sport.